The Graphing of Difference: Numerical Mediation and the Case of Google's Knowledge Graph. (October 2016) - Monea, Alexander
This article offers a critical examination of contemporary graph databases, such as Google's Knowledge Graph, from the perspective of media theory, philosophy of difference, and epistemology. It argues that the fundamental data structure of the "triple, " in essence a subject-predicate-object statement, constitutes a problem immanent to the database itself. The article begins with a brief meditation on numerical mediation before examining the emergence of the Knowledge Graph through Google's research publications. It then moves on to demonstrate that a logic of representation underlies all graph databases, and that this logic of representation operates similarly to Aristotle's theory of perception and categorization. Drawing on Gilles Deleuze's criticism of Aristotle, this article argues that graph databases fall into similar traps of identity and representation and are unable to understand difference in itself. In closing, it offers an initial diagnosis of the limitations of graph databases, and more specifically how Google's graph database's inability to interrogate difference in itself leaves the Knowledge Graph unable to represent, let alone participate in, the discovery and invention of the new.